TOONATRIC ON REDUCING SYSTOLIC BLOOD PRESSURE IN HYPERTENSION PATIENTS - Salsabila, Afifah; Windiarti, Sri Endang; Arwani, Arwani (Jurnal Riset Kesehatan, 2025)
Hypertension is a significant global health concern, contributing to high mortality rates and increased risks of cardiovascular disease. In Indonesia, hypertension prevalence has reached over 33% of the adult population. Non-pharmacological interventions, such as nature sound therapy and isometric handgrip exercises, have shown promise in managing hypertension by reducing systolic blood pressure. This study introduced Tool Nature Sound and Isometric Handgrip (Toonatric), an innovative tool combining nature sound therapy and isometric handgrip exercises. This research employed a quasi-experimental design with 66 elderly hypertensive patients divided into intervention and control groups. The intervention group used Toonatric for 30 minutes daily over 5 days, while the control group continued standard care. Pre and post-intervention blood pressure measurements were analyzed using Wilcoxon and Mann-Whitney tests due to non-normal data distribution. Results indicated a significant reduction in systolic blood pressure in the intervention group (p = 0.000), with an effect size of Cohen’s d = 0.48, demonstrating a moderate clinical effect. Toonatric has the potential as a complementary tool for managing hypertension in elderly, combining psychological and physical benefits. Further research should focus on long-term effects, broader populations, and usability improvements for clinical and home settings.